Le shopping mall comme moment urbain - Laure Assaf (Ateliers d'Anthropologie)
Since the 2000s, the introduction of shopping malls in the United Arab Emirates has been contributing to new urban development trends, whose objective is to implement economic diversification and turn the Emirati city into a global destination. The ethnographic study of their uses shows how they contribute to producing new forms of coexistence between the highly diverse populations residing in these cities. Within the malls, residents negotiate their modes of interaction and behavior towards population categories they rarely encounter elsewhere—a process that is not without conflict. Emirati malls are also social scenes where people develop new forms of sociability, in turn shaping new subjectivities—particularly in the case of young adults who use these spaces to perform the role of modern, cosmopolitan subjects. The connection between malls and urban development, as well as the generational dimension of the practices carried out there, eventually lead us to question the specific temporalities of the mall as an urban form and a moment in Emirati urbanity.